Coping Stres Dalam Aktivitas Belajar Pada Sekolah Menengah Atas Negeri di Kecamatan Telanaipura Kota Jambi - Hendra, Robi; Setiyadi, Bradley; Bahri, Zainul (Indonesian Educational Administration and Leadership Journal (IDEAL), 2022)
The purpose of the study was to determine the stress level of students, to find out the factors that cause learning stress and to find out how to reduce learning stress at State High Schools in Telanaipura District, Jambi City. The dimensions studied in seeing coping stress are divided into several dimensions including a) Self-activity, b) Planning, c) Self-control, d) Seeking instrumental social support, e) Seeking emotional social support, f) Acceptance, g) Religiosity. This study uses a mixed research design or mixed method. The mixed methods research approach is an approach that combines or associates qualitative and quantitative forms. In this study, a measurement scale is used, namely the Likert scale to see coping stress and the stress level measurement scale using a semantic differential behavioral scale model. This research was carried out at SMAN in Telanaipura Time Quantitative research at SMAN 5 is March 6 to March 8, 2020 The population used in this study is class XII students, school principals and Counseling Guidance (BK) teachers at SMAN 5 and SMAN 10 respectively, with 1500 respondents. The results and findings of this study were 97 (62%) were classified, categorized as high stress levels in learning activities at school. There are 53 (38%) students, categorized as low stress level and the efforts or strategies taken by students in dealing with stress are divided into several dimensions including self-activity 3.84, planning 3.90, self-control 3.80, seeking instrumental support 3 .78, seeking emotional support 3.95 acceptance 3.77 and religiosity 3.78 and the average stress reduction effort made by students 3.83 is in the high category which can be opened in academic activities in high school schools in Telaipura sub-district, Jambi city dense with a high level of stress students are able to cope with stress well